ANALISA KARAKTERISTIK PEMBEDA ANTARA WIRAUSAHAWAN DAN NON-WIRAUSAHAWAN - Budi, Budi (Fakultas Ekonomi dan Bisnis, 2018)
Some basic elements in entrepreneurship education are: characters, skills, processes and behaviors. Therefore, it is important to know what are the characteristics that distinguishing between an entrepreneur and non-entrepreneur, and then infuse these distinguishing characteristics to the participants in entrepreneurship education. This study aims to investigate the difference characteristics between entrepreneurs and non-entrepreneurs in general. Specifically those differences are furtherly divided into several categories, such as between women, between men, between social educational background, between educational background in engineering and design. The methodology used is quantitative research, instrument development is done by reviewing the literature. Respondents were alumni of University of Bunda Mulia, whereas data collection was conducted through a questionnaire distributed online. Data was analyzed using SPSS software. And Mann-Whitney's test were performed. Results showed that the characteristics that distinguishing entrepreneurs and non-entrepreneurs in general are oriented opportunities, for distinguishing men entrepreneurs and non-entrepreneurs is oriented opportunities, for distinguishing entrepreneurs and non-entrepreneurs with educational background in engineering and design is self confident. Eventually and there are no characteristics differences between women entrepreneurs and non enterpreneurs, and social educational background entrepreneurs and non-entrepreneurs. There are not many distinguished characteristics between an entrepreneur and non-entrepreneur in reality raises a question of whether there are other more dominant factors beside psychological characteristics to turn entrepreneurial intentions into entrepreneur in reality. More extensive research is needed to determine whether other exogenous variables such as perceived subjective norms or propensity to act more decisive to turn entrepreneurial intentions into entrepreneur in reality.